Armed Non-State Actors and Cultural Heritage in Armed Conflict. Issue 4 (14th December 2017) - Lostal, Marina; Hausler, Kristin; Bongard, Pascal
Abstract: This article presents the preliminary findings of a scoping study that Geneva Call is conducting to understand the existing dynamics between armed non-state actors (ANSAs) and cultural heritage. Geneva Call is a Swiss-based non-governmental organization dedicated to promoting the respect of international humanitarian law by ANSAs. The study centres on three case studies—Syria, Iraq, and Mali—on which information has been obtained through desk and field research, interviews with ANSAs operating in those countries, and with leading organizations committed to the protection of cultural heritage, globally or regionally. The article first maps the various attitudes of ANSAs toward cultural heritage, highlighting both positive and negative examples from current practices. Then it analyzes the response of specialized organizations to the impact of ANSAs on cultural heritage and their level of engagement with these actors on cultural heritage issues. Finally, the conclusion offers some tentative recommendations to enhance the respect of cultural heritage by ANSAs in non-international armed conflicts.